Significance of cytogenetic-risk categories and refined international prognostic scoring system for overall survival in primary myelofibrosis: A single-center experience - Djordjević, Vesna; Denčić-Fekete, Marija; Jovanović, Jelica; Soldatović, Ivan; Janković, Gradimir; Bogdanović, Andrija (Vojnosanitetski pregled, 2021)
Background/Aim. Primary myelofibrosis (PMF) is a chronic, malignant hematological disease characterized by a leucoerythroblastic blood picture, anisopoikilocytosis teardrop-shaped erythrocytes, different degrees of bone marrow fibrosis and hepatosplenomegaly due to extramedullary hematopoiesis. Among genetic specificities of the disease, those that stand out are chromosomal aberrations in pathological, myeloid blood cells. The aim of this study was to examine the prognostic significance of clinical, hematologic and cytogenetic parameters in PMF. Methods. A retrospective study included 144 patients with PMF. Karyotypes were analyzed using conventional cytogenetic methods. Results. The chromosome examinations were successful in 126 (88%) patients and failed in the remainder ones (12%). Karyotype was abnormal in 36/126 (29%) subjects at presentation. The most frequent changes included +9, 13q- and 20q- (28%). Other abnormalities were: aberrations of chromosome 18 and 16, deletions (9q-, 12p-, 7q-, 5q-, 6q-, 8q-), trisomies (+1q, +8, +10, +21), monosomies (-7, -11), 3q inversion and loss of Y chromosome. We detected four novel balanced translocations in PMF: t(17;22)(q11;q13), t(15;17)(q22;q25), t(9;12)(q22;q24) and t(2;4)(q21;p16), one constitutional translocation-rob(13;14)(q10;q10) and some new karyotype anomalies ˗ deletion of both homologues, hyperdiploidy and the coexistence of unrelated pathological clones. Conclusion. Chromosomal aberrations had a significant influence on overall survival of patients with PMF according to the refined cytogenetic-risk of the International Prognostic Scoring System (Refined CIPSS) (p = 0.004). Our patients matched the pattern of chromosome aberrations usually observed in PMF but some newly registered, balanced translocations and other rare karyotype anomalies were recorded as well.